Steering surface topographies of electrospun fibers: understanding the mechanisms - Gökçe Yazgan (Nature Portfolio, 2017)
Abstract A profound understanding of how to tailor surface topographies of electrospun fibers is of great importance for surface sensitive applications including optical sensing, catalysis, drug delivery and tissue engineering. Hereby, a novel approach to comprehend the driving forces for fiber surface topography formation is introduced through inclusion of the dynamic solvent-polymer interaction during fiber formation. Thus, the interplay between polymer solubility as well as computed fiber jet surface temperature changes in function of time during solvent evaporation and the resultant phase separation behavior are studied. The correlation of experimental and theoretical results shows that the temperature difference between the polymer solution jet surface temperature and the dew point of the controlled electrospinning environment are the main influencing factors with respect to water condensation and thus phase separation leading to the final fiber surface topography. As polymer matrices with enhanced surface area are particularly appealing for sensing applications, we further functionalized our nanoporous fibrous membranes with a phosphorescent oxygen-sensitive dye. The hybrid membranes possess high brightness, stability in aqueous medium, linear response to oxygen and hence represent a promising scaffold for cell growth, contactless monitoring of oxygen and live fluorescence imaging in 3-D cell models.